Pendampingan Penjaringan Calon Perangkat Desa Mangunrejo dalam Rangka Menghasilkan SDM Pemerintahan Desa yang Inovatif - Sri Handayani; Mashur Hasan Bisri; Putri, Sukma Ayu (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2023)
Creating civil servants that can be innovative, creative and adaptive in technology and science, needs improvement from various aspects, as example, networking and screening of prospective village officials which can be done using several representative methods. The goals is filtrating to obtain prospective village officer who supporting village’s basic needs. As one of the villages in Kepanjen District, Malang Regency, Mangunrejo Village has committed to starting digitalization era. All information which relating to public services, village activity agendas, news, etc. has been disseminated on Mangunrejo Village official website which can be accessed by all people. This commitment needs supported from village officer who competent technological tools, adaptive, creative and innovative. Now, village officer cant only having a humanist approach and actions towards their community members, but also knowing how to quickly respond to user needs without taking a long time and long-winded. The output targets in this activity are collaborating with Mangunrejo Village, especially with their Village Leader and its staff, to finding an innovative, adaptive and creative village’s civil servants through several multistages tests which held within transparently, fairly and effectives principles.